Usage consideration of FFlib Apex Common framework in Salesforce enterprise applications - Liutenko, Iryna Victorivna; Sanko, I. V. (Одеська національна академія харчових технологій, 2020)
These theses describe the peculiarities of using the FFlib Apex Common framework when developing Salesforce applications (CRM systems). The use of thisframework will increase the assessment of the developed software for such an important quality characteristic as scalability.
Keywords: framework; enterprise applications; project team; business; low-buddgget pprojects; creating software